SCHOOL SAFETY STUDY: TALKING ABOUT DISASTER RISK REDUCTION KNOWLEDGE IN PUBLIC AND PRIVATE PRIMARY SCHOOLS, ARE THEY DIFFERENT? - Widowati, Evi; Wahyuningsih, Anik Setyo; Indrawati, Fitri; Sulistyani, Ummi Nur Laila (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
Indonesia is one of the countries prone to disasters. Children are one of the vulnerable groups to become victims when a disaster strikes. At the same time, not all public and private schools in Indonesia have good resilience in facing disasters, including not being able to provide adequate disaster education for students. This study aimed to determine whether there are differences in the implementation of disaster education between public and private primary schools and to find out whether there is a relationship between the availability of information on disaster, ownership of procedures for evacuation, training, and disaster response simulations with the knowledge of disaster risk reduction (DRR) of school communities. This quantitative research used a cross-sectional study approach. The data analysis used the Mann-Whitney test for the difference test and the Spearman’s rank correlation coefficient (CC) test for the relationship test. The results of the analysis show that there is a significant difference in disaster knowledge between public and private primary schools (Sig. .014). Availability of disaster information (CC .461) and emergency simulation (CC .321) are priority factors in increasing the DRR knowledge of school residents in both public and the private primary schools.